2022
DOI: 10.3390/foods11121711
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Edible Oils by Fungal Lipases: An Effective Tool to Produce Bioactive Extracts with Antioxidant and Antimicrobial Potential

Abstract: Hydrolysis of olive, rapeseed, linseed, almond, peanut, grape seed and menhaden oils was performed with commercial lipases of Aspergillus niger, Rhizopus oryzae, Rhizopus niveus, Rhizomucor miehei and Candida rugosa. In chromogenic plate tests, olive, rapeseed, peanut and linseed oils degraded well even after 2 h of incubation, and the R. miehei, A. niger and R. oryzae lipases exhibited the highest overall action against the oils. Gas chromatography analysis of vegetable oils hydrolyzed by R. miehei lipase rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Putting all these together, R. miehei was considered to be the best option as it is already widely used by the food industry in multiple biotechnological processes (including lipid processing like alcoholysis reactions and FA esterification) [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putting all these together, R. miehei was considered to be the best option as it is already widely used by the food industry in multiple biotechnological processes (including lipid processing like alcoholysis reactions and FA esterification) [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the FA that are mainly esterified at the PL sn-1 position, like SFA, are more susceptible to their action, which might explain the extensive hydrolysis of palmitic acid (16:0) both in PC and PE. In their work, Kotogan et al [ 66 ] and her co-workers found that the type and amount of released FA were different depending on the source of the oil. For rapeseed oil, these authors reported a significant increment of unsaturated FA like oleic (18:1 n-9), linoleic (18:2 n-6) and linolenic acids (18:3 n-3), without remarkable changes in SFA contents.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors also identified and quantified tocopherols in Brazil nuts oil, such as Funasaki et al 40 activity of lipase enzymes is reported in the literature for sunflower seeds storage. 41 These lipases, which are produced by fungi present on the surface of the nuts, 42,43 are responsible for enzymatic oxidation or hydrolytic rancidity, 44 another radical-based reaction that can occur on nuts. 1 Zanotto et al 43 have isolated from Brazil nuts phytopathogenic fungi that showed hydrolytic activity.…”
Section: Influence Of the Active Packaging And Temperature On The Oxi...mentioning
confidence: 99%
“…Although there are studies on the ability of lipases to release fatty acids in some edible oils, the bioactive properties of the produced hydrolysis products have not yet been characterized as far as we know. Kotogán et al (2022) have showed that the R. miehei lipase treatment may be a suitable approach to developing bioactive lipid mixtures with antioxidative and antimicrobial activities from vegetable and fish oil substances. The health‐protective fatty acid compounds obtained after an extraction can be used as additives in functional food products.…”
Section: Biotechnological Applicationsmentioning
confidence: 99%